Impact of social media on Academic Performance of Students - Goet, Joginder (KIC International Journal of Social Science and Management, 2022)
The study aims to determine the effect of the growing use of social media variables on the Academic Performance of Students of various colleges. Based on multi-stage sampling, a sample of 360 students has been selected. The questionnaire has been used as an instrument for data collection. Ninety per cent of questionnaires were returned from respondents on which correlational and causal research designs were applied for data analysis. The results represent that the association of various social media factors have been positive, and there has been a significant impact of social media factors on the Academic Performance of Students. In recent times, it encourages the future and career development of students. Social media variables like Video Watching, Media Sharing, Internet Searching and Video Gaming capture the students’ attention for study and affect their Academic Performance.